(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Emotiveness and evaluation are important characteristics of English emotive adjectives. They are used for a codified expression of emotions in communication, producing an emotional effect on a recipient.